2021
DOI: 10.1136/thoraxjnl-2020-216013
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microbial cell-free DNA is associated with inflammatory host-responses in severe pneumonia

Abstract: Host inflammatory responses predict worse outcome in severe pneumonia, yet little is known about what drives dysregulated inflammation. We performed metagenomic sequencing of microbial cell-free DNA (mcfDNA) in 83 mechanically ventilated patients (26 culture-positive, 41 culture-negative pneumonia, 16 uninfected controls). Culture-positive patients had higher levels of mcfDNA than those with culture-negative pneumonia and uninfected controls (p<0.005). Plasma levels of inflammatory biomarkers (fractalkine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…McfDNA species may reflect SI-causal pathogens (regardless of their viability in the bloodstream), but may also signify lung barrier disruption in patients with acute lung injury from COVID-19, or even gut barrier disruption in patients with circulatory shock and hypoperfusion. 14 Thus, positive mcfDNA calls should not be directly interpreted as evidence of superinfecting pathogens, but interpreted within the context of a critical illness with colonized mucosal surfaces by microbiota and impaired barrier function. The significant correlation between hcfDNA levels and RALE scores suggests that lung injury may account, at least in part, for the systemic levels of circulating hfcDNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…McfDNA species may reflect SI-causal pathogens (regardless of their viability in the bloodstream), but may also signify lung barrier disruption in patients with acute lung injury from COVID-19, or even gut barrier disruption in patients with circulatory shock and hypoperfusion. 14 Thus, positive mcfDNA calls should not be directly interpreted as evidence of superinfecting pathogens, but interpreted within the context of a critical illness with colonized mucosal surfaces by microbiota and impaired barrier function. The significant correlation between hcfDNA levels and RALE scores suggests that lung injury may account, at least in part, for the systemic levels of circulating hfcDNA.…”
Section: Discussionmentioning
confidence: 99%
“…14 For contextualization, we compared mcfDNA levels among subjects with COVID-19 with our previously published dataset of mechanically ventilated patients with and without pneumonia. 14 To profile the host response, we measured plasma levels of nine prognostic biomarkers (eight interleukin [IL]-6, IL-8, pentraxin-3, procalcitonin, receptor for advanced glycation end products [RAGE], angiopoietin-2 (Ang-2), suppression of tumorigenicity [ST]-2, and tumor necrosis factor receptor [TNFR]-1 with Luminex, and surfactant Protein D [SPD] with ELISA; R&D Systems, Minnesota). We measured plasma SARS-CoV-2 viral levels (vRNA) following RNA extraction and qPCR amplification with a sensitive in-house method.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22][23] Studies have reported that plasma mNGS has moderate sensitivity and high specificity for invasive mold infections in pulmonary patients 23 and is highly consistent with BALF mNGS in patients with severe pneumonia. 19 Yang et al 24 also found a novel link between plasma mNGS and systemic inflammation in patients with severe pneumonia. However, two other studies suggested that BALF mNGS is more sensitive than plasma mNGS in patients with pneumonia, and concordance between paired BALF and plasma was not sufficient.…”
Section: Introductionmentioning
confidence: 93%